2016
DOI: 10.1161/hypertensionaha.116.07008
|View full text |Cite
|
Sign up to set email alerts
|

Telmisartan Ameliorates Nephropathy in Metabolic Syndrome by Reducing Leptin Release From Perirenal Adipose Tissue

Abstract: Abstract-Metabolic syndrome (MetS) is associated with nephropathy. Along with common risk factors such as hypertension and hyperglycemia, adipocytokines released from perirenal adipose tissue (PRAT) are implicated in the pathogenesis of MetS nephropathy. The study was designed to elucidate the adverse effects of PRAT-derived leptin on nephropathy and to determine whether the angiotensin II type 1 receptor antagonist telmisartan exerts a renoprotective effect by decreasing the PRAT-derived leptin level in the h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
34
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(36 citation statements)
references
References 40 publications
0
34
0
1
Order By: Relevance
“…First, PUFT secretes paracrine substances with functional or metabolic renal action that could play a key role in the development of nephropathy. In a previous study, Li et al found that perirenal adipose tissue exacerbated renal vascular remodeling in rats through the production of leptin, a well‐known adipocytokine with an adverse effect on kidney, and different paracrine substances were observed by other authors to have a similar action . In addition, excessive free fatty acids released from PUFT could escape into the kidney and lead to renal lipotoxicity by increasing intracellular fatty acids metabolites .…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…First, PUFT secretes paracrine substances with functional or metabolic renal action that could play a key role in the development of nephropathy. In a previous study, Li et al found that perirenal adipose tissue exacerbated renal vascular remodeling in rats through the production of leptin, a well‐known adipocytokine with an adverse effect on kidney, and different paracrine substances were observed by other authors to have a similar action . In addition, excessive free fatty acids released from PUFT could escape into the kidney and lead to renal lipotoxicity by increasing intracellular fatty acids metabolites .…”
Section: Discussionmentioning
confidence: 95%
“…In a previous study, Li et al 32 found that perirenal adipose tissue exacerbated renal vascular remodeling in rats through the production of leptin, a well-known adipocytokine with an adverse effect on kidney, and different paracrine substances were observed by other authors to have a similar action. 27,32 In addition, excessive free fatty acids released from PUFT could escape into the kidney and lead to renal lipotoxicity by increasing intracellular fatty acids metabolites. 31,46,47 PUFT might also reflect renal function better than other indices of visceral fat due to the different venous drainage of perirenal adipose tissue: In fact, it drains into the caval system, whereas the venous circulation of the visceral fat around omentum (detected by RA) is part of the portal axis, and this might produce different systemic effects.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our result also demonstrated increased plasma Ang II level in HFD-fed mice. It has been reported that Ang II involves in HFD-induced hypertension through various pathways including leptin-related nephropathy [26], restoration of sympathetic over-reactivity [27], megalin-dependent uptake of angiotensinogen into adipocytes [28], vascular oxidative stress and endothelial dysfunction [29], and increased VSM reactivity [131430]. Increased VSM reactivity to Ang II in HFD-fed individuals is reported to be attributed to increased expression of AT1R and ACE 2 [13], and reactive oxygen species (ROS) overproduction and enhanced release of Ca 2+ induced by Ang II [14].…”
Section: Discussionmentioning
confidence: 99%